THE MEDIATION ROLE OF THE MULTIFOCAL TRUST IN THE RELATIONSHIP BETWEEN JUSTICE AND ORGANIZATIONAL COMMITMENT IN MUHAMMADIYAH UNIVERSITIES - waskito, jati; Riani, Asri Laksmi; Suyono, Joko; Setiawan, Akhmad Ihwan (Benefit: Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study was to determine the level of perceived fairness, trust and organizational commitment for contract employees. Specifically, this study aims to examine the mediating role of trust (towards leaders and organizations) on the relationship between organizational justice and organizational commitment. The respondents in this study were temporary lecturers at the five best Muhammadiyah private universities in Indonesia. The survey results found 182 lectures who were willing to become respondents. The results of this study that organizational justice cannot increase organizational commitment. Nevertheless, distributive and procedural justice can increase their trust in organizations. Similarly, informational justice can increase trust in supervisors. The results of this study showed the important role of trust in management and trust in supervisors as a mediator in the relationship between organizational justice and organizational commitment.